Аллилуйя женщине-цветку: [новеллы] / Рене Депестр - Депестр Рене (Панорама романов о любви, 1997)
Экземпляры: Ф. 10 (20200522) / Инвентарный номер: 47804 / Цена: 10.00 / Сис.шифр: 84(4Фра) / Авт.знак: Д 35 / ГРНТИ: 17.82 / ББК: 84(4Фра)